Effects of perioperative interventions for preventing postoperative delirium: A protocol for systematic review and meta-analysis of randomized controlled trials. Issue 29 (23rd July 2021) - Li, Xia; Wang, Yanting; Liu, Jie; Xiong, Yue; Chen, Shiqiang; Han, Jingjing; Xie, Wanli; Wu, Qingping
Abstract: Background: Postoperative delirium (POD) not only increases the medical burden but also adversely affects patient prognosis. Although some cases of delirium can be avoided by early intervention, there is no clear evidence indicating whether any of these measures can effectively prevent POD in specific patient groups. Objective: The aim of this meta-analysis was to compare the efficacy and safety of the existing preventive measures for managing POD. Methods: The PubMed, OVID (Embase and MEDLINE), Web of Science, and the Cochrane Library databases were searched for articles published before January 2020. The relevant randomized controlled trials (RCTs) were selected based on the inclusion and exclusion criteria. Data extraction and methodological quality assessment were performed according to a predesigned data extraction form and scoring system, respectively. The interventions were compared on the basis of the primary outcome like incidence of POD, and secondary outcomes like duration of delirium and the length of intensive care unit and hospital stay. Results: Sixty-three RCTs were included in the study, covering interventions like surgery, anesthesia, analgesics, intraoperative blood glucose control, cholinesterase inhibitors, anticonvulsant drugs, antipsychotic drugs, sleep rhythmic regulation, and multi-modal nursing. The occurrence of POD was low in 4 trials that monitored the depth of anesthesia with bispectral index during the operation ( P < .0001). Two studies showed that supplementary analgesia was useful for delirium prevention ( P = .002). Seventeen studies showed that perioperative sedation with α2 -adrenergic receptor agonists prevented POD ( P = .0006). Six studies showed that both typical and atypical antipsychotic drugs can reduce the incidence of POD ( P = .002). Multimodal nursing during the perioperative period effectively reduced POD in 6 studies ( P < .00001). Furthermore, these preventive measures can reduce the duration of delirium, as well as the total and postoperative length of hospitalized stay for non-cardiac surgery patients. For patients undergoing cardiac surgery, effective prevention can only reduce the length of intensive care unit stay. Conclusion: Measures including intraoperative monitoring of bispectral index, supplemental analgesia, α2 -adrenergic receptor agonists, antipsychotic drugs, and multimodal care are helpful to prevent POD effectively. However, larger, high-quality RCTs are needed to verify these findings and develop more interventions and drugs for preventing postoperative delirium. Abstract : Supplemental Digital Content is available in the text